HISTORICAL AND CULTURAL IMPLICATIONS OF HUMAN IMMUNODEFICIENCY VIRUS (HIV) AND WOMEN’S RIGHTS IN NIGERIA: A CONTEXTUAL CLARIFICATION - Olayemi Jacob, Ogunniyi; Akinola George, Dosunmu (European Scientific Journal, ESJ, 2014)
Nigerian women are undeniably Nigerians. This bestow on their rights and privileges enjoyed by other Nigerians. However, over a decade now, numerous cases of women’s right violation such as acid baths, murder of women, rape, widow abuse, and physical assaults have occurred in Nigeria (Okeke, 2008). Ironically, it is only extreme cases of women’s right violation which results in death or permanent disability that earn media attention and police interest. Similarly, it is instructive to note that the sexual practices of male partners are likely to be the primary source of risk to women of infection with HIV or the STDs. Women (including wives) are often not in the position to negotiate safe sex and may have not yet imbibed the condom culture as a means of protection against AIDS and other sexually transmitted infections (Ndubusi 2007). Human immunodeficiency virus in Nigeria remain a major public health crisis and since its first reported case in 1999 as Monjok, Smesny and Essien (2000) noted, the prevalence of HIV among women attending antenatal clinics in Nigeria rose from less than 1% to 21%, context of a phenomenon which has assumed a frightening dimension in recent times. This article seeks to examine the cultural context of stigma on the rights of women living with HIV in Nigeria bringing into recommendation the enforcement of women’s right as human rights as the opposite will stultify the attainment of Millennium Development Goals (MDGs) and general development.